2019
DOI: 10.3390/toxins11110640
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence and Combinatory Effects of Alternaria Mycotoxins and Other Xenobiotics of Food Origin: Current Scenario and Future Perspectives

Abstract: Mycotoxins are low-molecular weight compounds produced by diverse genera of molds that may contaminate food and feed threatening the health of humans and animals. Recent findings underline the importance of studying the combined occurrence of multiple mycotoxins and the relevance of assessing the toxicity their simultaneous exposure may cause in living organisms. In this context, for the first time, this work has critically reviewed the most relevant data concerning the occurrence and toxicity of mycotoxins pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 130 publications
0
56
0
3
Order By: Relevance
“…These peppermint teas were produced in Poland, and our results were in good agreement with the data provided by Zimowska (2007), who reported the typical prevalence of both Alternaria and Phoma species in cultivated peppermint plants [ 38 ]. There are insufficient data on potential human infections due to Phoma species, whereas the potential risks of Alternaria fungi related to the production of toxic contaminants are an emerging issue [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These peppermint teas were produced in Poland, and our results were in good agreement with the data provided by Zimowska (2007), who reported the typical prevalence of both Alternaria and Phoma species in cultivated peppermint plants [ 38 ]. There are insufficient data on potential human infections due to Phoma species, whereas the potential risks of Alternaria fungi related to the production of toxic contaminants are an emerging issue [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review, Crudo et al (2019) suggested that Alternaria toxins commonly co-occur with AFs and emerging ENNs in different condiments [ 39 ]. Co-occurrence with AFs was found in 73% ( n = 16) of the samples of the 22 teas with both observed Alternaria toxins.…”
Section: Discussionmentioning
confidence: 99%
“…As pathogens, they affect many crops including grains, oil seeds, spices, and various fruits and vegetables, and may thus enter the food chain. Due to their growth even at low temperature, Alternaria fungal species are also responsible for spoilage of commodities during refrigerated transport and storage [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Some toxins such as alternariol (AOH), alternariol monomethyl ether (AME), tenuazonic acid (TeA), and altertoxins were described to induce harmful effects in animals, including fetotoxic and teratogenic effects. Culture extracts of A. alternata but also AOH and AME were found mutagenic and clastogenic in various in vitro systems [ 2 , 3 ]. Considering their possible harmful effects, presence of these toxins in food may be considered as a serious threat to public health.…”
Section: Introductionmentioning
confidence: 99%
“…Kamle et al [ 12 ] summarize the effect of fumonisin on human health and the strategies to reduce the level of this toxin in food. A group of emerging mycotoxins, those produced by Alternaria , is the focus of Crudo et al [ 13 ], who analyze “the most relevant data concerning the occurrence and toxicity of mycotoxins produced by Alternaria spp., (….) alone or in combination with other mycotoxins and bioactive food constituents”.…”
mentioning
confidence: 99%